2021
DOI: 10.1186/s12875-021-01580-z
|View full text |Cite
|
Sign up to set email alerts
|

Euthanasia in advanced dementia; the view of the general practitioners in the Netherlands on a vignette case along the juridical and ethical dispute

Abstract: Background In the Netherlands, euthanasia has been regulated by law since 2002. In the past decade, a growing number of persons with dementia requested for euthanasia, and more requests were granted. A euthanasia request from a patient with advanced dementia (PWAD) can have a major impact on a general practitioner (GP). We aimed to get insights in the views of Dutch GPs on euthanasia concerning this patient group. Methods A postal survey was sent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This inconsistency may be explained by former studies claiming that cancer, more so than neurological diseases, is the most frequent cause for requests for EUT, probably due to cancer's high prevalence in the population and the elevated public awareness to this disease ( 9 , 10 ). Specifically, cancer is more prevalent than PD among older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inconsistency may be explained by former studies claiming that cancer, more so than neurological diseases, is the most frequent cause for requests for EUT, probably due to cancer's high prevalence in the population and the elevated public awareness to this disease ( 9 , 10 ). Specifically, cancer is more prevalent than PD among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…A Swiss study that identified trends of PAS among patients over 18 years in age (1999–2016; n = 6,553) found that cancer was the most common underlying disease ( n = 2,704, 41.3% of all PAS cases) and cancer patients were considerably younger than patients with other diseases (73 years vs. 80 years) ( 8 ). Schuurmans et al ( 9 ) report that in all countries where EUT is legalized, it primarily concerns patients with cancer. In addition, more favorable attitudes toward EUT were reported when patients had cancer in comparison to patients with mental illnesses such as schizophrenia or clinical depression ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physicians underline the importance of having the possibility to verify whether their patient still supports their AED, as people are known to adapt to new situations and tend to change or postpone their wish for euthanasia [ 4 , 8 , 37 ]. In addition, prior literature on the subject shows that physicians find it also difficult to assess the due care criterion ‘unbearable suffering with no future improvement’ in an incompetent patient with dementia [ 38 ]. Furthermore, the participants indicate the need for this ‘reciprocal communication’ in order to achieve a shared insight with their patient, which is referred to as ‘mutual understanding’ [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many doctors have personal objections related to PAD in patients with advanced dementia (Schuurmans et al 2021 ). Even physicians who are quite willing to engage with challenging requests, may find performing PAD on an incompetent adult who at the time of the euthanasia cannot consent to the procedure and who has been unable to communicate about his/her death wish for a period of time, a moral line they are unwilling to cross (Schuurmans et al 2019 ).…”
Section: Patients With Advanced Dementia: Ethical Concernsmentioning
confidence: 99%